2017
DOI: 10.1080/2162402x.2016.1277305
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating CD39+γδTregs are novel immunosuppressive T cells in human colorectal cancer

Abstract: Tumor microenvironment (TME) promotes immune suppression through recruiting and expanding suppressive immune cells such as regulatory T cells (Tregs) to facilitate cancer progression. In this study, we identify a novel CD39 C gdTreg in human colorectal cancer (CRC). CD39 C gdTregs are the predominant regulatory T cells and have more potent immunosuppressive activity than CD4 C or CD8 C Tregs via the adenosine-mediated pathway but independent of TGF-b or IL-10. They also secrete cytokines including IL-17A and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 49 publications
1
104
1
Order By: Relevance
“…Atsushi et al. proposed that CD39 was a candidate surface marker for regulatory γδ T cells in IL‐10 knockout mice, which has been confirmed by further in‐depth studies . Peters et al.…”
Section: Regulatory γδ Cellsmentioning
confidence: 91%
“…Atsushi et al. proposed that CD39 was a candidate surface marker for regulatory γδ T cells in IL‐10 knockout mice, which has been confirmed by further in‐depth studies . Peters et al.…”
Section: Regulatory γδ Cellsmentioning
confidence: 91%
“…37 In vivo tumor-infiltrating reg cells could be induced by IP-10 secreted by breast cancer cells 38 indicating that these cells may play an important role to induce the immunosuppressive microenvironment in human CRC. 40 Finally, as demonstrated by several studies on different cancer, T cells showed a dual role in tumor immunity and it seems clearly associated with their complex surrounding microenvironment, which influences T cell polarization.…”
Section: T Cellsmentioning
confidence: 91%
“…have identified a novel CD39 + γδreg cell population in CRC that exerts an immunosuppressive activity via the adenosine‐mediated pathway; these cells also secrete cytokines including IL‐17A and GM‐CSF that are able to chemoattract MDSCs, thus establishing an immunosuppressive network. Concerning their protumoral functions, the authors showed that CD39 + γδreg infiltration was positively correlated with the tumour node metastasis (TNM) stage and other unfavorable clinicopathological features, indicating that these cells may play an important role to induce the immunosuppressive microenvironment in human CRC …”
Section: γδ and Cancermentioning
confidence: 99%
“…Traxlmayr et al found during clinical trial studies that DC production of IL-12 and pyrophosphate activation can in fact induce regulatory γδ T cell responses capable of hampering the proliferative capabilities of tumor-specific CD4 and CD8 T cells (47). A recent study demonstrated that tumor-infiltrating CD39 + γδ T cells have potent immunosuppressive activity via secretion of adenosine in human colorectal cancer (48). More investigation is needed to better characterize which γδ T cell populations are capable of becoming regulatory and how these suppressive populations operate in situ .…”
Section: Tumor Promotion By Of γδ T Cellsmentioning
confidence: 99%